2020
DOI: 10.1177/1044207320943607
|View full text |Cite
|
Sign up to set email alerts
|

Parental Experiences of Engaging With the National Disability Insurance Scheme for Their Children: A Systematic Literature Review

Abstract: The Australian National Disability Insurance Scheme (NDIS) reached full national implementation in July 2019. It supports Australians with disabilities via individualized funding packages for disability-specific services and assistive technology. This systematic review of literature presents research describing the experiences of parents of children with disabilities in accessing and participating in the fledgling NDIS and makes recommendations to assist the Agency in better supporting new participant families. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The administrative burden associated with the NDIS has been well documented, for both scheme participants and service providers (Carey, Dickinson, Malbon, Weier, & Duff, 2020; Foley, Attrill, McAllister, & Brebner, 2020; Mavromaras, Moskos, Mahuteau, & Iskerwood, 2018; Olney & Dickinson, 2019). Research has shown that individualized funding schemes, which rely on participant and carer self‐advocacy and ability to navigate complex administrative systems, are more accessible for well‐educated, native English‐speaking, and assertive individuals and families (Heneker, Zizzo, Awata, & Goodwin‐Smith, 2017; Mavromaras et al, 2018; Owens et al, 2017; Russo, Brownlow, & Machin, 2020). This was likely a factor in some of the variation in support our respondents experienced with the NDIS during COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…The administrative burden associated with the NDIS has been well documented, for both scheme participants and service providers (Carey, Dickinson, Malbon, Weier, & Duff, 2020; Foley, Attrill, McAllister, & Brebner, 2020; Mavromaras, Moskos, Mahuteau, & Iskerwood, 2018; Olney & Dickinson, 2019). Research has shown that individualized funding schemes, which rely on participant and carer self‐advocacy and ability to navigate complex administrative systems, are more accessible for well‐educated, native English‐speaking, and assertive individuals and families (Heneker, Zizzo, Awata, & Goodwin‐Smith, 2017; Mavromaras et al, 2018; Owens et al, 2017; Russo, Brownlow, & Machin, 2020). This was likely a factor in some of the variation in support our respondents experienced with the NDIS during COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…While the NDIS has many benefits, it places significant responsibility on caregivers, particularly in advocating for their children and managing their plans. Families have also expressed some frustration that the scheme is tailored towards individual adults instead of families and carers (Russo et al, 2021 ). Collectively this body of evidence suggests that there are significant gaps in meeting caregivers’ support needs and well-being needs.…”
mentioning
confidence: 99%
“…This difficulty is worse for people with an intellectual/cognitive disability, complex needs, complex communication needs, Aboriginal and Torres Strait Islander people and people who speak English as a second language. [18][19][20][21] These barriers influenced the process of developing plans and whether participants felt supported, less anxious and listened to during the process. 19 Previous research in individualised planning with people with disability demonstrates the importance of skilled staff and a commitment to a person-centred approach.…”
Section: What Is Already Known On This Subject?mentioning
confidence: 99%
“…The research suggests that without an advocate or assistance to navigate the planning process, many people with disability and/or their carers find it difficult to articulate their needs and goals during this process. This difficulty is worse for people with an intellectual/cognitive disability, complex needs, complex communication needs, Aboriginal and Torres Strait Islander people and people who speak English as a second language 18‐21 . These barriers influenced the process of developing plans and whether participants felt supported, less anxious and listened to during the process 19…”
Section: Introductionmentioning
confidence: 99%